THU0646 HIGH LEVELS OF DAMAGE IN INFLAMMATORY RHEUMATIC DISEASES: A CLUE TO LOW RATES OF REMISSION AND LOW DISEASE ACTIVITY. (June 2019) - Castrejon, Isabel; Everakes, Sarah; Block, Joel; Khandelwal, Sonali; Nika, Ailda; Raghu, Padmanabhan; Pincus, Theodore
Abstract : Background: Despite introduction of powerful biologic medications over the last 2 decades, rates of remission and low disease activity rates in RA remain less than 50%. One possible basis is that measures and indices such as disease activity score 28 (DAS28) and clinical disease activity index (CDAI), while sensitive primarily to disease activity in clinical trial patients selected for high inflammatory activity, may also reflect clinically important joint damage and patient distress in unselected patients in routine care. Similar considerations may pertain to systemic lupus erythematosus disease activity index (SLEDAI), Bath ankylosing spondylitis disease activity index (BASDAI), and other measures and indices initially designed to assess disease activity. Levels of organ damage and patient distress, as well as inflammation, may be quantitated according to 3 physician (0-10) visual analog scales (VAS), in addition to physician global assessment VAS (DOCGL), scored in fewer than 10 seconds in routine care. Objectives: To test a hypothesis that damage and distress may be prominent in patients with inflammatory conditions, according to mean VAS for inflammation or reversible findings (DOCINF), damage or irreversible findings (DOCDAM), and distress (DOCSTR), e.g., fibromyalgia. Methods: All patients at one site complete a multidimensional health assessment questionnaire (MDHAQ), which includes patient global VAS (PATGL), at each visit in routine care. Physicians complete four 0–10 (none-highest) VAS for DOCGL, DOCINF, DOCDAM, and DOCSTR, and a query to estimate the proportion of clinical decisions (total=100%) attributed to each of the 3 findings. Patients were classified into various diagnostic groups, in which scores were analyzed according to mean and standard deviation. Results: Analyses included 563 patients (Table). Mean levels of DOCGL ranged from 3.2 to 5.2, and PATGL from 3.6 to 6.5, which might be interpreted to indicate high disease activity. Highest mean DOCINF scores were seen in patients with RA, SLE, vasculitis, polymyalgia rheumatica (PMR), spondyloarthropathy (SpA), and gout (2.2-2.8), while highest mean DOCDAM was seen in OA (4.9) and DOCSTR in FM (6.2) (Table). However, in RA, mean DOCDAM was 3.7 vs 2.4 for DOCINF. DOCDAM also was almost as high or higher than DOCINF in SLE, SpA, vasculitis, and gout. Mean estimates of distress were also ≥1.5 in patients with all inflammatory diagnoses. Conclusion: Rheumatologists estimated high levels of damage in patients with RA and other inflammatory rheumatic diseases, similar or higher than inflammation, as well as recognizable distress which may elevate measures such as tender joint count and PATGL. These findings may explain in part low rates of remission and low disease activity noted in RA and other inflammatory diseases, as index scores used to document improvement are not affected by anti-inflammatory therapy. Most rheumatology clinical quantitative measurement is directed to inflammatory activity. However, an estimate of damage and distress may clarify why many patients may appear to have suboptimal control of inflammatory activity despite aggressive treatment, including treat to target in RA. Disclosure of Interests: None declared